Doing emotional labour in the Fourth Industrial Revolution (4IR): is religious television a humanised workplace? - Nur Kareelawati Abd Karim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article examines the quality of work life in Islam-based television by focusing on the emotional wellbeing of television production workers. It identifies the extent of religious television a humanised workplace at the turn of the Fourth Industrial Revolution (4IR). The study draws upon literature from media sociology and cultural studies approaches to creative labour in two folds by addressing the implications of 4IR for 1) human (television production workers), including such concepts as human emotional and spiritual intelligence, and emotional labour, and 2) for the quality of work life in televi-sion production, through the discourses of human-robot interaction (HRI) and humanised workplace. The analyses of an ethnographic data gathered from television stations in London and Kuala Lumpur indicate that television production work demands a different degree of emotional labour, depending on their professional roles, tasks, and the genre that they produced. The study concludes that doing emotional labour in the 4IR requires television production workers to renegotiate their professional roles not only with other humans, but also with robots/machines as robots/machines have increas-ingly taken over their production tasks. Such forms of negotiation and the rise of robots/machines resulting from the 4IR do affect the quality of work life in religious television.